Nursing Students' Attitude towards Complementary and Alternative Healthcare - Gasperaitytė, Vakarė; Greičienė, Svetlana (Slauga. Mokslas ir praktika, 2022)
Complementary and alternative healthcare has become very popular over the last decade almost all over the world. In 2021, the law on complementary and alternative healthcare was issued in Lithuania, which granted the right to healthcare professionals to practice this activity; those who have completed nursing studies are among them.Aim of the study – to analyse the attitudes of general practice nursing students to complementary and alternative healthcare.Methods. probability sampling, simple random method was chosen for the selection of subjects. A quantitative research method, questionnaire, was used to prepare this thesis. The study involved 82 general practice first to fourth year nursing students, who completed the questionnaire that was sent to the email of Vilnius College.Results. 57% of the general practice nursing students indicated that they were only partially familiar with complementary and alternative healthcare, and as many as 68% of students know nothing about the law on this area. 26% fully agreed and 49% agreed that this area has a positive effect on the treatment of symptoms, and 30% fully agreed and 46% agreed that it effectively complements modern healthcare. 90% of students indicated that they would like to know more about complementary and alternative healthcare. 21% fully agreed and 51% agreed with the need for knowledge in this area for the future profession, while 18% fully agreed and 44% agreed that complementary and alternative healthcare should be included in the general practice nursing study programme.Conclusions: The majority of general practice nursing students are insufficiently informed about complementary and alternative healthcare, but they are more positive about this area of healthcare and its application both in the study programme and in future professional practice.
Keywords: alternative medicine; nurses